ARTIFICIAL IN INTELLECT KNOWLEDGE DESCRIBE MODELS (Web of Technology: Multidimensional Research Journal, 2024)
This in the article artificial in intellect knowledge describe models through new views are logical conclusions , knowledge describe language , thinking fields in general when knowledge base in formation different to views attention to give need about, the results branched models using to conclude such as intellects more development can In the real process event and circumstances each one to the details price gave without reasoning by doing to see that's it with together to the situation right approach get time from demand come out to approach forms this while a person in his life important foundation will be.